2020
DOI: 10.29289/25945394202020200007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of breast cancer subtype on pathological complete response

Abstract: Objective: To compare the rates of pathological complete response (pCR) after treatment with neoadjuvant chemotherapy, in the different subtypes of breast cancer in patients followed at the Mastology Service of Hospital do Servidor Público Estadual. Methods: Descriptive and retrospective study, in which medical records of 213 patients diagnosed with breast cancer and submitted to neoadjuvant chemotherapy were reviewed, from February 2011 through January 2018. Histological data collected were: hormone receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…Failure to PCR is related to unfavorable prognosis in TNBC and HER-2+ tumors, but not in most luminal patients 29 . In fact, studies have indicated that luminal patients tend to present a favorable prognosis, although they are less responsive to chemotherapy, with relatively lower chances of achieving PCR, thus reflecting the uncertain correlation between PCR and long-term outcomes in luminal patients 16 .…”
Section: Causes Of Complete Pathological Response Failuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to PCR is related to unfavorable prognosis in TNBC and HER-2+ tumors, but not in most luminal patients 29 . In fact, studies have indicated that luminal patients tend to present a favorable prognosis, although they are less responsive to chemotherapy, with relatively lower chances of achieving PCR, thus reflecting the uncertain correlation between PCR and long-term outcomes in luminal patients 16 .…”
Section: Causes Of Complete Pathological Response Failuresmentioning
confidence: 99%
“…Factors related to the highest probability of PCR include TNBC tumors, HER-2+, high rate of cell proliferation (Ki67), and high degree of nuclear and ductal histology. Usually, patients with positive hormone receptor (RH+) have worse rates of PCR 12,29,30 . Currently, the rates of PCR are higher in TNBC patients, reaching 64.8% due to the use of immunotherapy with Pembrolizumab combined with chemotherapy 27 , and in HER-2+ due to double blockage with trastuzumab and pertuzumab associated with chemotherapy 20 (Table 3).…”
Section: Causes Of Complete Pathological Response Failuresmentioning
confidence: 99%